2017
DOI: 10.1130/g38800.1
|View full text |Cite
|
Sign up to set email alerts
|

Coupling leeside grainfall to avalanche characteristics in aeolian dune dynamics

Abstract: Avalanche (grainflow) processes are fundamental drivers of dune morphodynamics and are typically initiated by grainfall accumulations. In sedimentary systems, however, the dynamism between grainfall and grainflow remains unspecified because simple measurements are hampered by the inherent instability of lee slopes. Here, for the first time, terrestrial laser scanning is used to quantify key aspects of the grainfall process on the lee (slip face) of a barchan sand dune. We determine grainfall zone extent and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 21 publications
(16 reference statements)
5
54
1
Order By: Relevance
“…While the Maspalomas observations did not include a study of grain‐flow behaviour under a variety of wind conditions, the data agree well with the behaviour observed by Nield et al . () during stronger wind velocities. The wind velocity at the study site, adjusted to a height of 0·5 m, was approximately 8·6 m sec −1 and exhibited a high frequency of grain‐flow activity, where some grain flows occurred simultaneously or shortly after one another, or in ‘multiple families of failures’.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…While the Maspalomas observations did not include a study of grain‐flow behaviour under a variety of wind conditions, the data agree well with the behaviour observed by Nield et al . () during stronger wind velocities. The wind velocity at the study site, adjusted to a height of 0·5 m, was approximately 8·6 m sec −1 and exhibited a high frequency of grain‐flow activity, where some grain flows occurred simultaneously or shortly after one another, or in ‘multiple families of failures’.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Nield et al . () observed that with increasing wind velocities, the length and thickness of grain flows also increased. Additionally, the entrainment of sediment as grain flows travel down the slipface may vary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations